PERLINDUNGAN HUKUM KONSUMEN PENGGUNA APLIKASI E-COMMERCE TERHADAP KASUS PENYALAHGUNAAN AKUN DALAM KONSTRUKSI HUKUM ITE - Swanasti Djatu Dianti (2023)
The development of increasingly advanced technology has led to changes in people's lifestyles in many aspects, one of which is the emergence of online-based buying and selling applications or e-commerce. With this convenience, it turns out that there are new problems, namely account abuse. The problems discussed in this research are the factors that cause account abuse and the legal protection of e-commerce user consumers against account abuse cases in constructing the Electronic Information and Transaction Law (ITE). This research uses the juridical-normative research method. The results show that the factors causing account abuse are divided into 3 (three) types, namely internal factors, external factors, and other factors. The three kinds of factors are interrelated to cause account abuse. E-commerce user consumers are entitled to legal protection against cases of account abuse or phishing in the form of preventive legal protection and repressive protection. Preventive legal protection is obtained through the Electronic Information and Transaction Law (ITE Law) and the Personal Data Protection Law (PDP Law). As for repressive legal protection, both the ITE Law and the PDP Law allow consumers who are victims of account abuse to file a lawsuit, either criminally or civilly. Dispute resolution can be through arbitration, court, or other alternative dispute resolution institutions under the provisions of the applicable laws and regulations. About this, the researcher argues that an active role is needed from consumers, e-commerce platform providers, the government and relevant law enforcement officials to prevent and reduce the number of victims of account abuse in Indonesia.